Writing the Lives of Others: Storytelling and International Politics. (September 2016) - Daigle, Megan
This article explores practices of writing deployed in an attempt (sometimes futile) to mitigate and interrogate the relationship between researcher and informant across the unequal relations of power, economic disparities, and cultural divides – factors that create a partial and committed position for the author. In the process, and through the lens of an ethnographic study of sexual-affective economies in contemporary Cuba, storytelling emerges as a method and methodology for International Relations that facilitates (re)presentation of interviews that are unstructured, contingent, and difficult. Storytelling as a method and methodology reveals the multiplicity, contingency, and uncertainty of the research process, questioning the incitements to detachment and objectivity on which IR methodologies are built. Thus, narrative writing proves invaluable for expressing how the international acts on bodies (and vice versa), and for relating personal experiences of repression and resistance, joy and pain, in an international frame. Far from a merely stylistic choice, storytelling bears real ethical and political implications – for the research produced and for the individual subjects implicated in its production. Along the way, practices of writing themselves come to the fore, as academic conventions fall away and stories surface. Storytelling itself thus elaborates on the possibilities inherent in more creative, less structured, and more interpretive writing across the field of international politics.